The Effects of Various Doses of Azadirachta indica A. Juss. Seed Cake against Aphis gossypii (Glover) and Growth Characters of Red Chili Plants (Capsicum annuum L.) - Ardi Zulfikar Muchlis (CROPSAVER, 2021)
Neem plant is used as plant-based insecticide because all parts of the plant have insecticides activities. The utilization of neem plants as plant-based insecticides is generally only in the seed parts, but the extraction of neem seed extract has not been used because it is considered as waste. The utilization of neem seed cake as a natural insectiside is one way to recycle neem seed cake which is known to contain active ingredients of neem seed oil. Apart from its use as an insecticide, neem seed cake can also be used as an organic fertilizer. This study aimed to determine the effect of application of various doses of neem seed cake to A. gossypii on chili plants. The experiment used a randomized block design with 7 treatments and 4 replications. The treatments included control, neem seed cake doses of 25 gr, 50 gr, 75 gr, 100 gr, 125 gr, and a comparative treatment of carbofuran active ingredients. A. gossypii imago were introduced in 20 red chili plants per plant. The results showed the application of a dose of 50 gr of neem seed cake per polybag effectively suppressed A. gossypii populations and gave the best effect on some chili plant growth characters such as leaf chlorophyll content, plant height, leaf hardness of chili plant and levels of N element absorbed.